2013
DOI: 10.1186/1687-1847-2013-48
|View full text |Cite
|
Sign up to set email alerts
|

Existence results for fractional q-difference equations with nonlocal q-integral boundary conditions

Abstract: In this paper, we discuss the existence of positive solutions for nonlocal q-integral boundary value problems of fractional q-difference equations. By applying the generalized Banach contraction principle, the monotone iterative method, and Krasnoselskii's fixed point theorem, some existence results of positive solutions are obtained. In addition, some examples to illustrate our results are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…El-Shahed and Al-Askar [20] studied the existence of multiple positive solutions to the nonlinear q-fractional boundary value problems by using GuoKrasnoselskii's fixed point theorem in a cone. Zhao et al [30] showed some existence results of positive solutions to nonlocal q-integral boundary value problem of nonlinear fractional q-derivatives equation using the generalized Banach contraction principle, the monotone iterative method, and Krasnoselskii's fixed point theorem.…”
Section: Introductionmentioning
confidence: 99%
“…El-Shahed and Al-Askar [20] studied the existence of multiple positive solutions to the nonlinear q-fractional boundary value problems by using GuoKrasnoselskii's fixed point theorem in a cone. Zhao et al [30] showed some existence results of positive solutions to nonlocal q-integral boundary value problem of nonlinear fractional q-derivatives equation using the generalized Banach contraction principle, the monotone iterative method, and Krasnoselskii's fixed point theorem.…”
Section: Introductionmentioning
confidence: 99%
“…For details, see [1][2][3]. Recently, a great deal of work has been done in the study of the existence and uniqueness of solutions to nonlinear fractional differential equations (see [1][2][3][4][5][6][7][8][9][10][31][32][33] and the references therein). Some classical tools have been used to investigate such problems in the literature, such as some fixed point theorems in cones, the coincidence degree theory of Mawhin, and the method of upper and lower solutions with the monotone iterative technique.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to prove existence theorems are based on Krasnoselskii fixed-point theorem, the lower and upper solution method, the critical point theory, and fixed-point theorem on cones. [16][17][18][19][20][21][22][23][24][25] However, most of the above-mentioned papers have studied the boundary value problems within Caputo fractional operators. The initial value problems involving fractional q-difference equations defined via Riemann-Liouville settings have rarely been under investigation.…”
Section: Introductionmentioning
confidence: 99%